2020
DOI: 10.1021/acs.jpclett.0c02204
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Control over Molecular Aggregate Assembly Enables Tunable Excitonic Properties across the Visible and Near-Infrared

Abstract: Specific molecular arrangements within H-/J-aggregates of cyanine dyes enable extraordinary photophysical properties, including long-range exciton delocalization, extreme blue/red shifts, and excitonic superradiance. Despite extensive literature on cyanine aggregates, design principles that drive the self-assembly to a preferred H- or J-aggregated state are unknown. We tune the thermodynamics of self-assembly via independent control of the solvent/nonsolvent ratio, ionic strength, or dye concentration, obtaini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…To probe the aggregate morphologies of the new pentamethine dyes, we both screened 2a and 2b at a constant concentration and varied the methanol/water ratio, as well as varied the concentration at a constant methanol/water ratio. 34 Absorbance spectra for monomers and aggregates of different compounds are shown in Figure 2A. In this exploration, we found that the pentamethine dye aggregates display similar photophysical properties to the trimethine dyes, forming two primary aggregates (confirmed by non-negative matrix factorization, Figure S3) depending on the concentration and methanol ratio.…”
mentioning
confidence: 71%
“…To probe the aggregate morphologies of the new pentamethine dyes, we both screened 2a and 2b at a constant concentration and varied the methanol/water ratio, as well as varied the concentration at a constant methanol/water ratio. 34 Absorbance spectra for monomers and aggregates of different compounds are shown in Figure 2A. In this exploration, we found that the pentamethine dye aggregates display similar photophysical properties to the trimethine dyes, forming two primary aggregates (confirmed by non-negative matrix factorization, Figure S3) depending on the concentration and methanol ratio.…”
mentioning
confidence: 71%
“…To probe the aggregate morphologies of the new pentamethine dyes, we both screened 2a and 2b at varied concentrations while maintaining a constant methanol/water ratio (Figure 2A). 35 Aggregates of each chromophore were prepared by first creating a stock solution of the dye in methanol. To a small volume of this stock solution was added ultrapure H2O.…”
Section: Resultsmentioning
confidence: 99%
“…Using this approach, we were able to stabilize the 2D sheet-like morphology of all the dyes studied here (SI Figure S2). 36 We also include the well-known dye 3,3'-bis(4-sulfobutyl)-5,5',6,6'-tetrachloro-1,1'-diethylbenzimidacarbocyanine, sodium salt (TDBC), commonly used in photonic applications. 37,38 All 2D aggregates are prepared by injecting a methanol solution of the dye in water or aqueous NaCl (see experimental section for exact conditions), followed by equilibration in the dark for 24 h. By changing the dye lengths as well substitutions on the central position of the cyanine bridge (Figure 3a), we afford extended 2D aggregates with different brick lengths and slips.…”
Section: Resultsmentioning
confidence: 99%
“…48 Although, this is unlikely in our case, since all aggregates had up to micron scale sizes as seen from cryoEM images (SI Figure S2). 36 Screening aggregate geometries using stochastic modeling of the Hamiltonian: In Figure 5a-b, we…”
Section: Fwhm (B)mentioning
confidence: 99%